Online support groups offer low-threshold backing for family and friends of patients with prostate cancer - Ihrig, Andreas; Maatouk, Imad (European journal of cancer care, 2019)
A prostate cancer diagnosis affects not only the patients but also their family and friends. We performed a secondary analysis of a survey of users of the largest German online support group (OSG) for prostate cancer. We collected socio-demographic, psychological and disease-related data over a three-month period in 2013. Among 769 participants with a complete questionnaire, 686 were patients, and 83 were family members and friends of other patients. The family and friends group comprised 33% spouses, 31% children and 36% people with other relationships to the patient (“others”). Compared to the patient group, the family and friends group showed higher scores for anxiety and depression and described a higher rate of metastatic disease in the patients with whom they had a relationship. The children of patients showed the highest psychological burden based on their scores for anxiety and depression. Only 7% of spouses and none of the children attended face-to-face support groups, compared to 70% of people in the “others” group. OSGs offer low-threshold support for family members and friends; specifically, they meet the needs of spouses and children who do not attend face-to-face support groups. To improve counselling efforts, physicians should be aware of this online resource.
First published: 20 December 2018
Gesehen am 14.05.2019